Handbook of materials selection - Kutz, Myer
"An innovative resource for materials properties, their evaluation, and industrial applications. The Handbook of Materials Selection provides information and insight that can be employed in any discipline or industry to exploit the full range of materials in use today-metals, plastics, ceramics, and composites. This comprehensive organization of the materials selection process includes analytical approaches to materials selection and extensive information about materials available in the marketplace, sources of properties data, procurement and data management, properties testing procedures and equipment, analysis of failure modes, manufacturing processes and assembly techniques, and applications. Throughout the handbook, an international roster of contributors with a broad range of experience conveys practical knowledge about materials and illustrates in detail how they are used in a wide variety of industries. With more than 100 photographs of equipment and applications, as well as hundreds of graphs, charts, and tables, the Handbook of Materials Selection is a valuable reference for practicing engineers and designers, procurement and data managers, as well as teachers and students"--